1991
DOI: 10.1093/ajcn/54.2.386
|View full text |Cite
|
Sign up to set email alerts
|

Methionine kinetics in adult men: effects of dietary betaine onl-[2H3-methyl-1 -13C]methionine1–3

Abstract: The effects of a daily 3-g supplement of betaine on kinetic aspects of L-[2H3-methyl-1-13C]methionine (MET) metabolism in healthy young adult men were explored. Four groups of four subjects each were given a control diet, based on an L-amino acid mixture supplying 29.5 and 21.9 mg.kg-1.d-1 of L-methionine and L-cystine for 4 d before the tracer study, conducted on day 5 during the fed state. Two groups received the control diet and two groups received the betaine supplement. Tracer was given intravenously (iv)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
42
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 34 publications
9
42
0
Order By: Relevance
“…We have sought to monitor methionine cycle activity in maternal and fetal tissues of the pregnant rat by infusing L- [1-13 C,5-methyl- 2 H 3 ]methionine (21,22). This tracer was infused into rats offered diets differing in folate, choline, and methionine content at various stages of pregnancy (days 11, 19, and 21 of gestation).…”
mentioning
confidence: 99%
“…We have sought to monitor methionine cycle activity in maternal and fetal tissues of the pregnant rat by infusing L- [1-13 C,5-methyl- 2 H 3 ]methionine (21,22). This tracer was infused into rats offered diets differing in folate, choline, and methionine content at various stages of pregnancy (days 11, 19, and 21 of gestation).…”
mentioning
confidence: 99%
“…This enzyme, present primarily in the liver and kidney, is induced by betaine and can remethylate up to 25% of total homocysteine flux. 12 Betaine improved biochemical control in previous studies of patients with B6-nonresponsive C␤S deficiency. 13 Subsequent studies confirmed their observations that betaine treatment decreased total plasma homocysteine, in both plasma and cerebrospinal fluid.…”
mentioning
confidence: 82%
“…Indeed, the betaine content of infant formulas were reported to be within the range of breast milk, which was largely dependent on maternal betaine intakes (Sakamoto et al, 2001). Taken together, all of the reported estimates of betaine intake are well below supplemental levels that often provide 3--6 g betaine/d Ronge and Kjellman, 1996;Storch et al, 1991). However, because there is no dietary betaine requirement, it is unclear how variable intakes of this methyl donor affect methyl metabolism, or if there is a demand for dietary betaine in early life.…”
Section: Betainementioning
confidence: 95%
“…For example, in men supplemented with 3 g betaine/d under otherwise normal dietary conditions, the whole body rate of remethylation was unchanged despite increased transmethylation and decreased protein synthesis (Storch et al, 1991). This is confusing due to convincing evidence that betaine is effective at enhancing remethylation in adults (Mudd et al, 1980;Mudd and Poole, 1975) and protein deposition in swine (Fernández--Fígares et al, 2002).…”
Section: Betainementioning
confidence: 99%
See 1 more Smart Citation